2018
DOI: 10.1371/journal.pone.0190945
|View full text |Cite
|
Sign up to set email alerts
|

Opaque16, a high lysine and tryptophan mutant, does not influence the key physico-biochemical characteristics in maize kernel

Abstract: The enhancement of lysine and tryptophan in maize is so far basedon opaque2(o2) mutant, that along with the endosperm-modifiersled to development of Quality Protein Maize[QPM]. Though many mutants improving the endospermic protein quality were discovered, they could not be successfully deployed. Recently discovered opaque16 (o16)mutant enhances the lysine and tryptophan content in maize endosperm. In the present study, the influence of o16 on the endosperm modification was analyzed in four F2 populations, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…This indicates the role of modifiers in regulating amino acid biosynthesis (Pandey et al, ). Recently, novel opaque16 ( o16 ) was pyramided with o2 in the QPM hybrids for increasing amino acids in the endosperm (Sarika et al, ). Thus, combination of suitable gene(s) with o2 can potentially increase the level of lysine and tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the role of modifiers in regulating amino acid biosynthesis (Pandey et al, ). Recently, novel opaque16 ( o16 ) was pyramided with o2 in the QPM hybrids for increasing amino acids in the endosperm (Sarika et al, ). Thus, combination of suitable gene(s) with o2 can potentially increase the level of lysine and tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…Rosales et al 28 and Sarika et al 29 used the nonhydrolytic NIRS method to determine the protein, tryptophan, and lysine content of 266 samples of quality protein maize that has on average twice the tryptophan content of normal maize. The authors suggest that the efficient NIRS method is preferable to wet chemistry methods for the analysis of large numbers of samples generated in plant breeding programs.…”
Section: The Analysis Of Tryptophan In Food Body Fluids and Tissuesmentioning
confidence: 99%
“…The authors suggest that the efficient NIRS method is preferable to wet chemistry methods for the analysis of large numbers of samples generated in plant breeding programs. Sarika et al 29 found that despite the nutritional superiority of Opaque-16, a high-tryptophan and high-lysine maize mutant, the physico-biochemical characteristics of its endosperm are not affected.…”
Section: The Analysis Of Tryptophan In Food Body Fluids and Tissuesmentioning
confidence: 99%
“…Sarika et al used MABS to introgress o2 and o16 genes into different recurrent parents. Compared with the recurrent parents, the content of lysine and tryptophan increased by 76% and 91%, respectively [22,23]. Therefore, the polymerization of high-lysine mutant genes could improve the nutritional quality of corn seeds.…”
Section: Introductionmentioning
confidence: 99%